Acute knee joint rupture after yttrium 90 injection. Issue 1 (February 1975) - Davis, P; Jayson, M I
Abstract : Two cases of acute rupture of the knee joint are reported after the intra-articular injection of radioactive yttrium 90. It is suggested that this may be a complication of intra-articular radioactive injections.